The Coloring Graph of Complete Graphs - Harris, Haylee Aileen (The PUMP Journal of Undergraduate Research, 2019)
We study the coloring graph of the family of complete graphs and we prove that Cn(Kt) is regular, transitive, and connected when n>t. Also, we study whether Cn(Kt) is distance transitive or strongly regular, and find its diameter.